2013
DOI: 10.1007/s00268-013-2152-0
|View full text |Cite
|
Sign up to set email alerts
|

Stapleless Laparoscopic Splenectomy with Individual Vessel Dissection in Patients with Splenomegaly

Abstract: Stapleless LS for splenomegaly is feasible and safe in selected patients. It has advantages over traditional procedures using staples, at least in patients with benign splenomegaly. Patients with hematologic malignancy, BMI >30 %, coexistence of PH, and spleen weight >1,000 g are susceptible to bleeding during dissection of the splenic hilum, with use of IVD being relatively limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The maneuver using Endo GIA to staple and mutilate the splenic pedicle directly is called the primary pedicle dissection, while the secondary pedicle dissection refers to separation and ligation of second branches of the splenic pedicle individually [20] . Currently there are 3 ways to manipulate the splenic pedicle in total laparoscopic surgeries: (1) Ligating the second branches of the splenic pedicle with clips or threads of silk: A study reported by Tan et al [21,22] has introduced a method applying double ligation of proximal splenic vessel with a thread of silk and occlusion of distal part with a titanium clip, and they proved that it is feasible, effective and cheap; (2) manipulating the splenic pedicle with Endo GIA: it is simple, safe and effective, which make it the favorite method chosen by most doctors at home and abroad, though more expensive [20] ; (3) processing the splenic pedicle with LigaSure vessel-sealing equipment: it has been developed for the safe closure of arteries up to 7 mm in diameter [23] . But the data for venous closure are rare, some study stated that it can be used to close veins up to 12 mm in diameter [24] and can treat grades 3 and 4 of hemorrhoids [25] .…”
Section: Discussionmentioning
confidence: 99%
“…The maneuver using Endo GIA to staple and mutilate the splenic pedicle directly is called the primary pedicle dissection, while the secondary pedicle dissection refers to separation and ligation of second branches of the splenic pedicle individually [20] . Currently there are 3 ways to manipulate the splenic pedicle in total laparoscopic surgeries: (1) Ligating the second branches of the splenic pedicle with clips or threads of silk: A study reported by Tan et al [21,22] has introduced a method applying double ligation of proximal splenic vessel with a thread of silk and occlusion of distal part with a titanium clip, and they proved that it is feasible, effective and cheap; (2) manipulating the splenic pedicle with Endo GIA: it is simple, safe and effective, which make it the favorite method chosen by most doctors at home and abroad, though more expensive [20] ; (3) processing the splenic pedicle with LigaSure vessel-sealing equipment: it has been developed for the safe closure of arteries up to 7 mm in diameter [23] . But the data for venous closure are rare, some study stated that it can be used to close veins up to 12 mm in diameter [24] and can treat grades 3 and 4 of hemorrhoids [25] .…”
Section: Discussionmentioning
confidence: 99%
“…For the control of the vessels in the splenic hilum, we initially used a vascular stapler, and after 2006, we employed individual vessel dissection and clips, similarly to the method described by Tan in their paper published in 2013. 17 Similarly to Tan, we found the method to be safe, especially in the case of splenomegaly when the positioning of the stapler would be difficult because of the reduced space. There are papers about managing the splenic hilum with a…”
Section: The Effect Of the Learning Curve (Study Ii)mentioning
confidence: 75%
“…(Figure 2) For the control of the vessels in the splenic hilum, the Endo GIA stapler was used in the learning period until 2006, which was later replaced with individual vessel dissection and Hem-o-lok clip ligation. 17 The dissection of the hilum, similarly to the method of Tan, was performed from anterior to posterior and from inferior to superior directions, which made the identification of the vessels and the pancreas easy, and with which the risk of pancreatic injury could be minimized. (Figure 3) If the patient requires platelet transfusion, it should be administered after the ligation of the splenic artery.…”
Section: Surgerymentioning
confidence: 99%